Replacing conventional decontamination of hatching eggs with a natural defense strategy based on antimicrobial, volatile pyrazines. Issue 1 (December 2017) - Kusstatscher, Peter; Cernava, Tomislav; Liebminger, Stefan; Berg, Gabriele
Abstract The treatment of hatching eggs relies on classic yet environmentally harmful decontamination methods such as formaldehyde fumigation. We evaluated bacteria-derived volatiles as a replacement within a fundamentally novel approach based on volatile organic compounds (VOCs), which are naturally involved in microbial communication and antagonism due to their high antimicrobial efficiency. Pyrazine (5-isobutyl-2, 3-dimethylpyrazine) was applied passively and actively in prototypes of a pre-industry-scale utilization. Altogether, pyrazine decontamination rates of up to 99.6% were observed, which is comparable to formaldehyde fumigation. While active evaporation was highly efficient in all experiments, passive treatment showed reducing effects in two of four tested groups only. These results were confirmed by visualization using LIVE/DEAD staining microscopy. The natural egg shell microbiome was characterized by an unexpected bacterial diversity ofPseudomonadales, Enterobacteriales, Sphingomonadales, Streptophyta, Burkholderiales, Actinomycetales, Xanthomonadales, Rhizobiales, Bacillales, Clostridiales, Lactobacillales, andFlavobacteriales members. Interestingly, we found that especially low pyrazine concentrations lead to a microbiome shift, which can be explained by varying antimicrobial effects on different microorganisms.Micrococcus spp., which are linked to embryonic death and reduced hatchability, was found to be highly sensitive to pyrazines. Taken together, pyrazine application was shown to be a promising, environmentally friendly alternative for fumigation treatments of hatchery eggs.